2016
DOI: 10.1037/pas0000173
|View full text |Cite
|
Sign up to set email alerts
|

The sweet spot of clinical intuitions: Predictors of the effects of context on impressions of conduct disorder symptoms.

Abstract: How people interpret a mental disorder symptom has been shown to depend on the contextual life factors surrounding its presentation. Specifically, people are more likely to judge a symptom as clinically relevant if that symptom presents in a high-risk environment (e.g., child associates with deviant peers) relative to a low-risk environment (e.g., child associates with normative peer group). Importantly, not all symptoms are influenced by context to the same extent, and there is low agreement across people as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…This type of nondiagnostic contextual information greatly swayed how individual symptoms of disorder were interpreted. In samples of both trained clinicians and laypeople, when a single symptom of a disorder was presented in an inconsistent context, people were significantly less likely to ascribe a disorder diagnosis to the child compared to when the exact same symptom was presented in a consistent context (De Los Reyes & Marsh, 2011;Marsh, Burke, & De Los Reyes, 2016;Marsh, De Los Reyes, & Wallerstein, 2014). From the perspective of the DSM, these findings are especially surprising because consistent context information could have provided the explanatory context to explain away a single symptom of disease and reduce people's ratings of disease likelihood.…”
Section: Empirical Articlementioning
confidence: 99%
“…This type of nondiagnostic contextual information greatly swayed how individual symptoms of disorder were interpreted. In samples of both trained clinicians and laypeople, when a single symptom of a disorder was presented in an inconsistent context, people were significantly less likely to ascribe a disorder diagnosis to the child compared to when the exact same symptom was presented in a consistent context (De Los Reyes & Marsh, 2011;Marsh, Burke, & De Los Reyes, 2016;Marsh, De Los Reyes, & Wallerstein, 2014). From the perspective of the DSM, these findings are especially surprising because consistent context information could have provided the explanatory context to explain away a single symptom of disease and reduce people's ratings of disease likelihood.…”
Section: Empirical Articlementioning
confidence: 99%
“…mental health concerns) versus environments containing no such risk factors(De Los Reyes & Marsh, 2011). More recent work indicates that effects of contextual information generalize to clinicians' judgments of other mental health domains (i.e., attention and hyperactivity; panic disorder), as well as laypeople's judgments(Marsh, Burke, & De Los Reyes, 2016;Marsh & De Los Reyes, 2018;Marsh, De Los Reyes, & Wallerstein, 2014).…”
mentioning
confidence: 99%
“…Existing research offers evidence that experienced clinicians are sensitive to the social context surrounding adolescent antisocial behavior, and that they judge youth as less likely to have a mental disorder when context suggests the behavior might be a normal reaction to a harsh environment, rather than irrational responses resulting from internal dysfunction (Hsieh 2001;Hsieh andKirk 2003, 2005;Pottick et al 2003Pottick et al , 2007Wakefield et al 2002Wakefield et al , 2006. Other research studies have found that clinicians differentially use contextual information to weigh the importance of symptoms in judging whether a youth should be considered as having a diagnosis of conduct disorder (De Los Reyes and Marsh 2011;Marsh et al 2016), and have demonstrated that contextual information not only influences how clinicians arrive at diagnoses, but can also influence their judgments about other aspects of the clinical encounter, such as prognosis, need for professional help, and appropriateness of medication .…”
mentioning
confidence: 99%